As reformas pombalinas da instrução pública e as ordens religiosas : o caso de Sergipe Del Rey - São José, Elisson Souza de (2023)
This work focuses on the relationship between the Pombaline reforms of public education and religious orders, and investigates how historiography has represented this relationship, observing the specific case of Sergipe Del Rey. In this way, it seeks to understand how the minister Sebastião José de Carvalho e Melo, better known as Marquis of Pombal, dealt with the Catholic religious orders: Jesuits, Oratorians, Franciscans, Carmelites and Benedictines, verifying to what extent their conflicts and agreements had repercussions in Brazilian and Sergipe education. To this end, a count was carried out in the catalog of theses and dissertations on the platform of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), with the intention of knowing which works have already been published and what were the subjects addressed in them. The research presents the Marquis of Pombal's relationship with Portuguese education, highlighting his dissatisfaction with the way of teaching and learning of the period, which was under the responsibility of the Jesuit priests. The replacement of the Ignatians by royal teachers, most of whom would be priests of other orders, was an attempt to fix the problem. However, other problems arose. Regarding Sergipe Del Rey, the thesis highlights the lack of interest of the religious and Portuguese authorities in sending qualified people to teach in the region, a problem that lasted for several decades, causing the non-compliance with the Pombaline educational reforms during the period he was in the Portuguese administration. The thesis shows how the plenipotentiary minister of King Joseph I related to the religious orders of his time, whether in terms of opposition, as was the case with the Jesuits, or in terms of collaboration, as with the oratorians. Supported by the theoretical support of cultural history, we will make use of the historiography of the period and other documentary, legislative, literary and epistolary sources, as well as compendiums and periodicals published both physically and digitally.